Manufacture and Analysis Performance of Injection Device System 4 Stroke Engine Againts Emissions - Cahyo, Bagus Dwi; Irawan, Bambang (CV. Creative Tugu Pena, 2023)
Electronic fuel injection is a mechanism of fuel injection by electronic in to combustion chamber with Electronic Control Unit (ECU) for process control enter and burning air-fuel mixture. Fuel injection system is a development of natural suction system which next five years will no longer be produced. Natural suction system produces high emissions due to inhomogenous the air-fuel mixture. The natural suction system still widely used and its possible that in the next five years it will no longer be produced. The purposes of the study are manufacture and redesign injection intake manifold by sand casting with alumunium material as a replacement of natural suction fuel system with Arduino AT-Mega 2560 as a microcontroller with crankshaft posistion sensor, unit sensor (manifold absolute pressure, throttle position, intake air themperature) to produce eficient emissions. The study method of analysis data for making conclusion is quantitive experiments twoway anova with two independent variables are (1) intake manifold type and (2) fuel flow rate volume against emissions. The study results are manufacture of injection intake manifold by using the sand casting method with aluminium material is simple mehod for changes to the injection system againts emissions with value CO 14,27%, HC 212 ppm, CO2 12,133 % and O2 6,270 %, intake manifold type and fuel flow volume significant againts emissions. Keywords: Injection Device System, Intake Manifold, Redesign, Emissions